The Problem of Unregistered Marriage (Siri) in Pati Coastal Java - A. Zaenurrosyid; Abd Kahfi; Ali Syafa’ (Al-Manhaj: Journal of Indonesian Islamic Family Law, 2021)
Dinamika hukum Islam mengalami tantangan beragam di Nusantara. Pernikahan di Pesisir Jawa menjadi problematis karena dilarang dalam hukum positif, namun dibolehkan dalam Islam. Penelitian ini dengan pendekatan kualitatif dalam perspektif sosio-normatif. Ditemukan beberapa kasus pernikahan bawah tangan di Pesisiran Jawa, Pati dengan keragaman alasan suami istri menikah dibawah tangan. Faktor yang dominan adalah persoalan ekonomi, hamil di luar nikah, maupun alasan study. (The dynamics of Islamic law face various challenges in the archipelago. Marriage on Marriage on the coastal Java becomes problematic because it is prohibited in positive law, but is allowed in Islam. This research applied a qualitative approach in a socio-normative perspective. Several Cases of underhand marriages have been found in coastal Java, Pati with a variety of reasons for husband and wife marrying on underhand. The dominant factors are economic problems, pregnancy out of wedlock, and study reasons.)